The Vanquishers - Bayron, Kalynn (Bloomsbury Children's Books, 2022)
In an alternate San Antonio, there have been no known cases of vampirism since a group of masked vampire hunters called the Vanquishers wiped out the last horde of the undead twenty years ago, but twelve-year-old Malika "Boog" Wilson's parents are not taking any chances, especially when Boog's new classmate Aaron goes missing.